Uncertain Transition: Judicial Disparity and the Limits of Supreme Court Circular Letters in the Era of Criminal Law Codification - Risma Yulestari; La Ode Muhamad Sulihin; La Ode Muhammad Ichsan; La Ode Muhammad Saleh Saputra; Alif Talib (Recht Studiosum Law Review, 2026)
The simultaneous implementation of the National Penal Code (Law Number 1 of 2023) and the New Code of Criminal Procedure (Law Number 20 of 2025) on January 2, 2026 marks a fundamental transformation in Indonesia’s criminal justice system, while also creating significant challenges in ensuring consistency of legal application during the transitional period. This study aims to identify the forms of judicial disparity, evaluate the effectiveness of Supreme Court Circular Letter Number 1 of 2026, and formulate an ideal model for ensuring legal certainty. The research employs a normative legal method using statute and conceptual approaches, supported by limited case and comparative approaches. The findings reveal three main forms of disparity, namely regime disparity, sentencing disparity, and procedural disparity, which stem from the ambiguity of transitional norms and the absence of detailed operational guidelines. Supreme Court Circular Letter Number 1 of 2026 is found to be insufficiently effective as a disparity-prevention instrument due to its limited normative authority, substantive scope, and implementation. Therefore, this study proposes a three-pillar model for ensuring legal certainty, consisting of strengthening normative instruments through a Supreme Court Regulation, establishing an inter-institutional coordination forum, and enhancing judicial interpretive capacity through continuing legal education. This model is expected to reduce disparity and promote fair legal certainty during the transitional period.